2002
DOI: 10.1902/jop.2002.73.8.906
|View full text |Cite
|
Sign up to set email alerts
|

Calculation of Simplified Single‐Root Surface Area From Simulated X‐Ray Projection

Abstract: The circumference of an elliptical object can be approximated from the projection data of this ellipse. Therefore, the surface area of a single tooth root may be estimated with clinically useful accuracy from the projection data.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 8 publications
0
4
0
Order By: Relevance
“…The RSA of a tooth with a single root was evaluated with clinical accuracy from the projection data7. However, another study concluded that a reliable appraisal of the RSA and BSH ratio could not be determined from 2D linear or area data8.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The RSA of a tooth with a single root was evaluated with clinical accuracy from the projection data7. However, another study concluded that a reliable appraisal of the RSA and BSH ratio could not be determined from 2D linear or area data8.…”
Section: Discussionmentioning
confidence: 99%
“…However, another study concluded that a reliable appraisal of the RSA and BSH ratio could not be determined from 2D linear or area data8. The inconsistent outcomes may be due to different sample sizes, appliances, methodologies, or statistical analyses78.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Meanwhile, the RSA is associated with tooth size, morphology, length, diameter, trunk width and the number of roots, so accurate measurement is di cult. Traditional measurement methods include lm forming method, image segmentation method and quality conversion method (Yamamoto et al, 2006) (Chen et al, 2002), but they all need to measure the extracted teeth.…”
Section: Introductionmentioning
confidence: 99%